Strengthening Ukhuwah Basyariyah Through Nyongkolan Tradition: A PAR Approach to Exploring the Local Wisdom of the Sasak Tribe in Lombok - Faisol; Syaiful Mustofa; Nurhadi; Mirel Imelda Sasella; Mahsa Nabilah Adynastiti; Nabilah Ulil Fikriya; Nevin Nismah; M Farid Ulinnuha (Dimas: Jurnal Pemikiran Agama untuk Pemberdayaan, 2024)
This research aims to explore the role of Nyongkolan tradition in strengthening ukhuwah basyariyah in Sasak community, Lombok, through Participatory Action Research (PAR) approach. The background of this research is the phenomenon of modernization that affects local traditions, such as the shift from traditional musical instruments to more modern ones, as well as reduced community participation. This activity involves observation and active participation of the community in the implementation of Nyongkolan, with a focus on strengthening the values of interfaith and social brotherhood. The results showed that Nyongkolan serves as an important tool for strengthening social relations between citizens and interfaith tolerance, creating a space for interaction between Muslims and non-Muslims. In addition, it raises people's awareness of the importance of preserving local wisdom, and gives them a sense of pride in their cultural identity. The research also identified challenges faced in preserving this tradition, including the changing preferences of the younger generation and the pressures of modernization. Community participation in this study confirms the importance of the Nyongkolan tradition in maintaining social cohesion amidst socio-cultural changes.